EFEKTIFITAS MODEL PEMBELAJARAN TEAM GAME TOURNAMENT (TGT) MENINGKATKAN BERPIKIR KRITIS SISWA - Aruna, Rezky Putri; Emiliannur, Emiliannur; Winarno, Nanang (Jurnal MIPA dan Pembelajarannya, 2024)
This research aimed at the effectiveness of the Team Game Tournament (TGT) learning model to improve students' critical thinking skills. at SMAN 1 Koto XI Tarusan. This study used a post-test-only control design with a quasi-experimental approach. The population in this study were all students of class XI IPA SMAN 1 Koto XI Tarusan. The research sample was divided into two groups, namely the experimental and the control. Sampling was done by simple randomization, especially for class X.E.5 and X.E.8. Data analysis used descriptive statistics, including normality test, homogeneity test, and t-test with a significance threshold of 0.05. The analysis results showed that the mean value of the TGT class was 81.11, which exceeded the mean value of the regular class which was 71.31. Since the L0 value is smaller than the Lt value, the normality test for each class shows that the data is normally distributed. Regarding homogeneity, both samples show homogeneous variance, because the Fh value of 0.544 is smaller than the Ft value of 0.554. The t-count value of 5.148 exceeds the t-table value of 1.999, based on the results of hypothesis testing using the t-test at the 0.05 significance level. It can be concluded TGT model is more effective for improving critical thinking skills